Morphology and phase stability of nitrogen-partially stabilized zirconia (N-PSZ) - Chung, TJ; Lee, JS; Kim, DY; Kim, GH; Song, H (AMER CERAMIC SOC, 2001)
The surface layer of yttria-doped tetragonal zirconia materials that have been heat-treated with zirconium nitride was observed to consist of a nitrogen-rich cubic matrix with nitrogen-poor tetragonal precipitates. The precipitates had a thin, oblate-lens shape, similar to those observed in magnesia-partially stabilized zirconia. Because of the fast diffusion of N4- ions, the precipitates grew rather large, up to similar to5 mum in length, and remained stabilized in the tetragonal form at room temperature. Because the nitrided layer grew in the two-phase field, the size and distribution of the precipitates each was very irregular. The nitrogen content was observed to determine the proportion of cubic and tetragonal phases in the same way as in conventional cation-stabilized partially stabilized zirconia. A ternary phase diagram for the zirconium(yttrium)-nitrogen-oxygen system was suggested to explain the concentration gradient in the cubic matrix and the phase distribution of the nitrided layer.
Keywords: DOPED TETRAGONAL ZIRCONIA; SYSTEM; TRANSFORMATION; NITRIDATION; ZRO2